Understanding Nauryz among Kazakhs and Nogais: the cyclical concept of time and cultural renaissance - Zeinullin, Raimbek; Kudaibergenova, Nazgul; Aidarbekov, Zeinabil; Kuranbek, Asset; Gabitov, Tursun (Frontiers in Communication, 2026)
This study investigates the Nauryz holiday in Kazakh and Nogai cultures, focusing on its cyclical conception of time and social-symbolic significance. Traditionally, Nauryz marks the transition from the old year to the new, restoring harmony in nature and society. Drawing on structural anthropology (C. Lévi-Strauss), functional anthropology (B. Malinowski), ritual theory (V. Turner), semiotics (Y. Lotman), and the invention of tradition (E. Hobsbawm), the research analyzes the holiday's mythological origins, symbolic structures based on binary oppositions (dark–light, winter–summer, stagnation–renewal), and its role in social integration. Despite restrictions during the Soviet era, Nauryz was preserved in collective memory and experienced a revival by the late 20th century. In contemporary urban settings, it functions as a key element of national identity formation, while also undergoing commercialization and adaptation to new sociocultural contexts. The study highlights how Nauryz mediates temporal, social, and ritual dimensions, connecting historical traditions with modern practices, and illustrates the resilience and reinterpretation of cultural knowledge. Comparative analysis of Kazakh and Nogai practices provides insights into the broader role of cultural festivals in maintaining community cohesion, negotiating historical transformations, and fostering social integration, demonstrating the dynamic interplay between tradition and contemporary cultural environments.